2020
DOI: 10.1097/prs.0000000000007245
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid in Infantile Craniosynostosis Surgery: Friend or Foe?

Abstract: Background: Recent studies support the prophylactic use of tranexamic acid during craniosynostosis surgery to reduce blood loss. The study aims to assess national trends and outcomes of tranexamic acid administration. Methods: The Pediatric Health Information System database was used to identify patients who underwent craniosynostosis surgery over a 9-year period (2010 to 2018). Search criteria included patients younger than 2 years with a primary diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…10 The most rigorous examination of the safety profile of tranexamic acid was from a multicenter collaborative study that evaluated perioperative complications in craniosynostosis surgery for patients receiving tranexamic acid (n = 1638). 13 In that study, the authors reported a 0.3% rate of seizures and no thrombotic events related to tranexamic acid. The rate of seizures was similar to the group those did not receive tranexamic acid.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…10 The most rigorous examination of the safety profile of tranexamic acid was from a multicenter collaborative study that evaluated perioperative complications in craniosynostosis surgery for patients receiving tranexamic acid (n = 1638). 13 In that study, the authors reported a 0.3% rate of seizures and no thrombotic events related to tranexamic acid. The rate of seizures was similar to the group those did not receive tranexamic acid.…”
Section: Discussionmentioning
confidence: 89%
“…Many craniofacial surgeons and pediatric anesthesiologists believe that despite the lack of strong evidence to support the use of TXA in craniofacial surgery, there are minimal side effects. 13,22 The studies included in our review did not report any side effects from TXA administration. However, there are many large sample studies from the adult population that reported deleterious sequelae from TXA use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrary to the results of the current study and previously reported research, 6,8 one meta-analysis on TXA in craniosynostosis surgery showed that increased use of TXA over a period of years increased blood transfusion and complication rates. 18…”
Section: Effect Of Txa On Blood Loss and Transfusion In Craniosynosto...mentioning
confidence: 99%